O wartościowaniu w reportażu - między refleksyjnością a osądem = On valuation in reportage - between reflectiveness and judgement - Dąbrowska, Dorota (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The aim of the article is to reflect on the issue of valuing reality in reportage - a problem closely related to the issue of the creator`s subjective stance and the adopted narrative strategy. The text has the character of a case study - it is focused on the analysis of two literary pieces of reportage - "Powietrze tu mokre" [Air is wet here] by Małgorzata Rejmer and "Zgorszenie polskie" [Polish scandal] by Mirosław Wlekły. The presented observations are intended to demonstrate that the typologies functioning in the Polish context and defining possible authorial attitudes in a reportage text do not reflect the complexity of literary manifestations of the genre.
Keywords: reportaż; wartościowanie; perswazja; obraza uczuć religijnych; reportage; evaluation; persuasion; offence against religious feelings